Clinical characterization and possible pathophysiological causes of the Deventilation Syndrome in COPD - Schellenberg, Mavi; Imach, Sandra; Iberl, Gabriele; Kirchner, Marietta; Herth, Felix; Trudzinski, Franziska (Scientific reports, 2022)
In daily routine, many COPD patients report early onset augmented dyspnea following use of NIV (Deventilation Syndrome, DVS) as a negative side-effect. The aim of this study is the clinical characterization and concrete definition of DVS. This monocenter prospective observational study collected demographic, physiologic and symptomatic data from 67 in-patients with severe COPD Gold III-IV and chronic hypercapnic failure before, during and after use of an established NIV. During their inpatient follow-up, we examined patients during the first hour after termination of nocturnal NIV. DVS was defined by the authors as an increase of ≥ 2 points on the Borg scale during the first 30 min in patients who reported repeated dyspnea after the use of NIV. We monitored cardiovascular and respiratory data and measured diaphragm excursion. Subjective dyspnea was documented by use of the Borg scale and questionnaires. In addition, respirator and demographic data were collected. DVS occurred in 58% of our COPD patient collective, showing predominant emphysema phenotype. Patients with DVS were more severely ill than non-DVS concerning bronchial obstruction (FEV1 0.6 vs. 0.8 l, p < 0.05) and hypercapnia during spontaneous breathing (pre NIV pCO2: 54.5 vs. 49.3 mmHg, p < 0.02). DVS patients showed significantly higher respiratory rates (RR) (20.1 vs. 18.1/min p < 0.05) after termination of NIV. This trial characterizes and defines early onset augmented dyspnea after the use of NIV, referred to as DVS. It is hereby brought to attention as a frequent side effect of long-term home ventilation and possible pathophysiologic mechanisms are elucidated.